A triple-amplification colorimetric assay for antibiotics based on magnetic aptamer–enzyme co-immobilized platinum nanoprobes and exonuclease-assisted target recycling. Issue 22 (7th October 2015) - Miao, Yangbao; Gan, Ning; Ren, Hong-Xia; Li, Tianhua; Cao, Yuting; Hu, Futao; Yan, Zhongdan; Chen, Yinji
Abstract : Herein, an ultrasensitive and selective colorimetric assay for antibiotics was developed based on magnetic aptamer–HRP–platinum composite probes and exonuclease-assisted target recycling. Abstract : Herein, an ultrasensitive and selective colorimetric assay for antibiotics, using chloramphenicol (CAP) as the model analyte, was developed based on magnetic aptamer–HRP–platinum composite probes and exonuclease-assisted target recycling. The composite probes were prepared through immunoreactions between the double stranded DNA antibody (anti-DNA) labeled on core–shell Fe3 O4 @Au nanoparticles (AuMNP-anti-DNA) as the capture probe, and the double stranded aptamer (aptamer hybrid with its complementary oligonucleotides) labeled on Pt@HRP nanoparticles as the nanotracer (ds-Apt–HRP–PtNPs). When the CAP samples were incubated with the probes for 30 min at room temperature, they could be captured by the aptamer to form a nanotracer–CAP complex, which was then released into the supernatant after magnetic separation. This is because the anti-DNA on the capture probes cannot recognize the single strand aptamer–CAP complex. The exonuclease I (Exo I) added into the supernatant can further digest the aptamer–CAP from the 3′-end of the aptamer and the CAP in the aptamer–CAP complex can be released again, which can further participate in a new cycling process to react with the probes. Pt and HRP in the nanotracer could both catalyze and dual amplify the absorbance at 650 nm ascribed to the 3, 3′, 5, 5′-tetramethylbenzidine (TMB)–H2 O2 system. Moreover, Exo I can assist the target recycling, which can further amplify the signal. Thus, the triple amplified signal can be quantified by ultraviolet-visible spectroscopy. The experimental results showed that the CAP detection possessed a linear range of 0.001–10 ng mL −1 and a detection limit of 0.0003 ng mL −1 (S/N = 3). The assay was successfully employed to detect CAP in milk, which is much more facile, time saving, and sensitive than the commercial ELISA kits.